Intervenciones basadas en mindfulness y bienestar en deportistas competitivos - Heredia Andujar, Ricardo (2021)
Competitive sport causes athletes to push their physical and psychological capacities to the limit in order to respond to the high level of demand and achieve their goals. However, in this process the global well-being and its dimensions are affected, having repercussions on the personal life and sports performance of the athlete. In recent years, mindfulnessbased interventions have proven effectiveness in different areas of psychology. In sports, research has been carried out with different intervention protocols, but with a greater emphasis on sports performance. For this reason, the present systematic review aims to identify whether Mindfulness-based interventions favor global well-being in competitive athletes. Through the PRISMA method a search is carried out, registering a total of 197 results, finally 7 research articles are reviewed. After reviewing the selected articles, there is mixed evidence regarding the effectiveness of Mindfulness-based interventions on the Global Well-being of competitive athletes.